IDEALS OF CONSTITUTION IN THE CONTEXT OF INDIAN CITIZENSHIP - MARWAHA, KANWAL (IJRDO - Journal of Social Science and Humanities Research, 2017)
It has been maintained and seen through the years in the light of the Constitution that absolute concepts of liberty and equality are very difficult to achieve in a modern welfare state. The enjoyment of these rights is subjected to the interest of the people and the state may therefore, at times, encroach on the domain of these rights for the common good or common interest, though that would depend upon the conditions and circumstances prevailing at a particular time. For instance, the welfare state attempts to satisfy “basic needs”. The word basic implies that over and above certain minima, it is open to some people to enjoy additional amenities, so that there will continue to be “haves‟ and “haves-not‟. The tendency sooner or later will be for the later to start insisting that some of the things which they would like, but do not have, are “basic” and hence “needs‟ and due “as of right‟. What is at time a luxury becomes at another time a necessity and need. For a welfare state to thrive and to maintain its constitutional goal, legislation aimed at social welfare is cardinal for the common good and common interest of the people. Directive Principles of State Policy and Fundamental rights together constitute the “conscience‟ of the Constitution and represents the basic rights inherent in human  beings in this country. There is no inherent conflict between them and both are equally inherent in promoting the aims and objectives of the Constitution. However, in translating them in socio economic reality some degree of compromise is inevitable.